2021
DOI: 10.1080/21504857.2021.1951788
|View full text |Cite
|
Sign up to set email alerts
|

Comics as a multimodal resource and students’ willingness to communicate in Russian

Abstract: The multimodal nature of daily interactions in the twenty-first century has led to growing calls for the inclusion of multimodal content like comics in foreign language classrooms. Such content, as opposed to traditional language textbooks, can boost learners' self-confidence and more effectively develop their multimodal competence, including their willingness to use foreign languages via diverse media. This article reports on an exploratory study involving a teacher of Russian as a foreign language (RFL) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…The focus on student engagement, deeper understanding of content, and self-reflection in the classroom serves as a driving force in the investigation of wholeclass practices that promote deeper learning. Furthermore, aligned with the results of this study, Calafato, R., &Gudim, F. (2022) andCastillo-Cuesta, L., &Quinonez-Beltran, A. (2022) state that digital comics can help students learn to read English stories by increasing their interest and intention.…”
Section: Figure 3 Mangatoon and Critical Readingsupporting
confidence: 86%
“…The focus on student engagement, deeper understanding of content, and self-reflection in the classroom serves as a driving force in the investigation of wholeclass practices that promote deeper learning. Furthermore, aligned with the results of this study, Calafato, R., &Gudim, F. (2022) andCastillo-Cuesta, L., &Quinonez-Beltran, A. (2022) state that digital comics can help students learn to read English stories by increasing their interest and intention.…”
Section: Figure 3 Mangatoon and Critical Readingsupporting
confidence: 86%
“…One example is the study by Calafato and Gudim (2022) that revealed how the consistent and systematic use of comic picture books as a multimodal resource in language classrooms can positively impact learners’ Willingness to Communicate (WTC) and even teachers’ professional development and interaction with students. It further contributes to a better understanding of how multimodal resources can be used to effectively develop students’ language skills and teachers’ pedagogical competencies.…”
Section: The Relationship Between Language Picture Books and Reciproc...mentioning
confidence: 99%
“…Calafato and Gudim (2022) noted that foreign language learners are often afraid to use the target language in the classroom, possibly due to concerns about their ability, lack of motivation, or cultural customs. Therefore, using comics as a multimodal resource, they investigated how their use affected Russian under the context of a foreign language learners’ willingness to communicate, and how this willingness to communicate manifested itself in the classroom, making students more willing to interact with the teacher in Russian.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…To this issue, comics can be used in a two-way learning process, namely as a teaching aid and as a learning medium that both teachers and students can use. Calafato & Gudim, (2022) define comic as a media, a "hybrid word-and-image form in which two narrative tracks, one verbal and one visual, spatially register temporality." Comics also encourage meaning-making and help teachers reduce students' cognitive load when learning vocabulary through reading activities.…”
Section: Introductionmentioning
confidence: 99%